2016
DOI: 10.1080/14656566.2016.1199684
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prevention of cytomegalovirus infection in heart and lung transplantation: an update

Abstract: While (Val)Ganciclovir remains the cornerstone of anti-CMV therapy, prolonged universal prophylaxis may expose a large number of patients to an excess of drug toxicity. Additional drugs with lower toxicity may be available in the context of anti-CMV prophylaxis, and effective CMV-risk stratification, by means of novel immune monitoring assays, which may help to customize the therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 113 publications
(117 reference statements)
2
15
0
Order By: Relevance
“…In fact, in all cases the first CMV DNAemia detection occurred after the discontinuation of prophylactic therapy (at a median time of 58 days posttransplant), while all preemptively managed patients experienced CMV infection in the early posttransplant period (i.e., within 1 month posttransplant). These findings are in accordance with those reported by other authors (3,13). However, to date there have not been any published randomized trials that directly compared preemptive therapy and prophylaxis in nonrenal solid-organ transplant recipients and there are no available reports of studies that clearly indicate which strategy is superior (3,13).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, in all cases the first CMV DNAemia detection occurred after the discontinuation of prophylactic therapy (at a median time of 58 days posttransplant), while all preemptively managed patients experienced CMV infection in the early posttransplant period (i.e., within 1 month posttransplant). These findings are in accordance with those reported by other authors (3,13). However, to date there have not been any published randomized trials that directly compared preemptive therapy and prophylaxis in nonrenal solid-organ transplant recipients and there are no available reports of studies that clearly indicate which strategy is superior (3,13).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in accordance with those reported by other authors (3,13). However, to date there have not been any published randomized trials that directly compared preemptive therapy and prophylaxis in nonrenal solid-organ transplant recipients and there are no available reports of studies that clearly indicate which strategy is superior (3,13).…”
Section: Discussionsupporting
confidence: 92%
“…Others have suggested that CMV disease is associated with and increased risk of mortality in heart transplantation . Although valganciclovir has not been shown to be superior to oral ganciclovir for CMV disease prevention, its significantly higher bioavailability and reduced pill burden make it the drug of choice . It is possible that quantitative improvements in CMV prevention and management in the valganciclovir era may be contributing to the era effects on mortality we observed.…”
Section: Discussionmentioning
confidence: 92%
“…In this study we decided to focus our attention on viral pathogens, as they are more difficult to detect compared to the bacterial ones, and since the biological samples are more likely to be naive of antimicrobial treatment, reducing this risk of bias. According to the literature, the prevalence of virus isolations on BAL fluid in patients with CAP or HAP is about 17%, but it is estimated to be higher in case of transplanted patients [44,45]. One of the drawbacks of BAL is the risk to obtain an inadequate specimen, due to the variability of the sampling procedure [46].…”
Section: Discussionmentioning
confidence: 99%